Penyuluhan tentang Pemantauan Tumbuh Kembang dan Pemberian Vitamin A pada Balita di Posyandu Kenanga Desa Mampir Kec. Cileungsi Kabupaten Bogor Tahun 2021 - Yulita Nengsih; Imelda Diana Marsilia (Jurnal Abdimas Kesehatan (JAK), 2021)
The quality of a child can be judged from the process of growth and development. The process of growth and development is the result of the interaction of genetic factors and environmental factors. Genetic/hereditary factors are factors related to genes originating from the father and mother, while environmental factors include the biological, physical, psychological, and social environment. Growth and development have increased rapidly at an early age, from 0 to 5 years. This period is often referred to as the "Golden Age" phase. Vitamin A is one of the vitamins that functions for the development and performance of various organs of the body, such as the eyes, skin, reproductive organs, and the immune system. To prevent vitamin A deficiency in toddlers, the Ministry of Health of the Republic of Indonesia conducts a program of providing vitamin A through posyandu. Based on the various solutions to the activities mentioned above, the output targets to be achieved in this program are formulated, including scientific publications and increasing parental knowledge. Types of counseling with participatory methods in Monitoring Growth and Giving Vitamin A to Toddlers. The activity was carried out in July at the Posyandu Kenanga, Mampir Village, Kec. Cileungsi, Bogor Regency. The results of this series of community service activities and parents turned out to be quite satisfactory, both in terms of mastery of the material that had been given. Participants' understanding was seen during the discussion on growth and development and giving Vitamin A questions and answers. It can be concluded that the counseling went well, parents were enthusiastic about the number of participants who attended and hoped that this activity could continue